“Inovasi Media Pembelajaran Berbasis Digital untuk Mendorong Literasi Manusia pada Siswa Sekolah Dasar dalam Menghadapi Tantangan Pendidikan 2025” - Nailah Zahiyyah; Alfitriana Purba; Dinda Nasution; Wan Muthia Habiby; Dilla Silvani; Sisilia Aginta br Tarigan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of digital technology has brought significant changes to elementary education, making digital literacy an essential competence for students. This study aims to examine innovations in digital-based learning media in improving elementary school students’ literacy and to identify effective models, challenges, and implementation strategies. This research employed a qualitative approach using a literature review method by analyzing relevant national and international journal articles. Data analysis was conducted descriptively through content analysis to identify patterns, trends, and key findings. The results indicate that digital learning media such as e-books, animated videos, educational games, digital teaching materials, and interactive media can enhance students’ digital literacy, reading interest, comprehension, and critical thinking skills. Effective digital-based learning models include blended learning and interactive learning approaches that promote active engagement, collaboration, and learning flexibility. However, the implementation of digital learning media in elementary schools still faces challenges, including limited access to devices and internet connectivity, insufficient teachers’ digital competence, and a lack of digital content aligned with the curriculum and local context. Therefore, comprehensive implementation strategies are required, including digital literacy training for teachers, the development of contextual digital learning media, improvement of technological infrastructure, and continuous supervision and character development. Overall, digital-based learning media innovations have strong potential to support the strengthening of elementary school students’ literacy in addressing contemporary educational challenges. Perkembangan teknologi digital membawa perubahan signifikan dalam pendidikan dasar, sehingga literasi digital menjadi kompetensi penting bagi siswa. Penelitian ini bertujuan mengkaji inovasi media pembelajaran berbasis digital dalam meningkatkan literasi siswa sekolah dasar serta mengidentifikasi model, tantangan, dan solusi implementasinya. Metode yang digunakan adalah pendekatan kualitatif melalui studi literatur denganmenelaah jurnal nasional dan internasional yang relevan. Analisis data dilakukan secara deskriptif menggunakan analisis isi untuk menemukan pola, kecenderungan, dan temuan utama. Hasil kajian menunjukkan bahwa media pembelajaran digital seperti e-book, video animasi, game edukasi, bahan ajar digital, dan media interaktif mampu meningkatkan literasi digital, minat membaca, pemahaman materi, serta kemampuan berpikir kritis siswa. Model pembelajaran berbasis digital yang efektif meliputi blended learning dan pembelajaran interaktif yang mendorong keterlibatan aktif, kolaborasi, dan fleksibilitas belajar. Namun, implementasi media digital di sekolah dasar masih menghadapi kendala berupa keterbatasan akses perangkat dan internet, rendahnya kompetensi digital guru, serta minimnya konten digital yang selaras dengan kurikulum dan konteks lokal. Oleh karena itu, diperlukan strategi implementasi yang komprehensif melalui pelatihan literasi digital bagi guru, pengembangan media pembelajaran kontekstual, peningkatan sarana prasarana teknologi, serta pengawasan dan pembinaan karakter. Secara keseluruhan, inovasi media pembelajaran berbasis digital berpotensi besar mendukung penguatan literasi siswa sekolah dasar dalam menghadapi tantangan pendidikan.